2013
DOI: 10.1155/2013/389672
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography as a Surrogate Marker for Evaluation of Treatment Response in Patients with Desmoid Tumors under Therapy with Imatinib

Abstract: We used 2-deoxy-2-[18F] fluoro-D-glucose (FDG) positron emission tomography (PET) to evaluate patients with desmoid tumors undergoing therapy with imatinib. The study included 22 patients with progressive disease (PD) of a biopsy proven desmoid tumor treated orally with imatinib 800 mg daily. Patients were examined using PET prior to onset of therapy and during treatment. Restaging was performed in parallel using computed tomography (CT) and/or magnetic resonance imaging (MRI). Outcome of 22 evaluable patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Combined 2-[ 18 F]-fluoro-2-deoxy-D-glucose (FDG) positron-emission tomography (PET) and computed tomography (CT) is not routinely used to assess or monitor DF; however, it has been proposed as a potential prognostic marker in discriminating responders from non-responders in patients undergoing treatment with tyrosine kinase inhibitors. 28 …”
Section: Guidelines For Imaging Biopsy and Specialist Referralmentioning
confidence: 99%
“…Combined 2-[ 18 F]-fluoro-2-deoxy-D-glucose (FDG) positron-emission tomography (PET) and computed tomography (CT) is not routinely used to assess or monitor DF; however, it has been proposed as a potential prognostic marker in discriminating responders from non-responders in patients undergoing treatment with tyrosine kinase inhibitors. 28 …”
Section: Guidelines For Imaging Biopsy and Specialist Referralmentioning
confidence: 99%
“…22 DF patients were analyzed using FDG-PET before imatinib treatment initiation and 4-6 weeks after start of treatment. A median decrease in the standardized uptake value (SUV) of 30% could be demonstrated and no patient showed an SUV increase [31]. Therefore, the authors suggested that PET may be used as a surrogate marker in order to predict the response to therapy early in the course of treatment and to help decide whether imatinib therapy should be continued [32,33].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Apart from the aforementioned forms of treatment for desmoid tumours, there is a wide array of other methods of treatment currently being investigated that have shown promising results. These include tyrosine kinase inhibitors such as imatinib or sorafenib, hormonal therapy such as tamoxifen, radio‐frequency ablation, percutaneous chemical ablation such as acetic acid and isolated limb perfusion for desmoid tumours in the extremities that are considered irresectable …”
Section: Management Options For Desmoid Tumoursmentioning
confidence: 99%